(untitled) (Fiep Bulletin - online, 2012)
The objective of this study was to evaluated the metal workload of the labor activity of public employees in the administrative sector from rectory of Universidade Estadual do Oeste do Paraná (Unioeste) Campus Cascavel. The present work is a quality-quantitative study of epidemiological type. The sample consisted of 35 employees. For data collection, it was used the NASA-TLX questionnaire to evaluate the mental workload of employees. The dimensions with the highest level of relevance were: mental demands and time pressure. And, with less relevance were physical demand and level of frustration. The total average of dimensions analyzed was 79, representing a high rate of mental workload and service time with moderate intensity (p = 0,0346). From the results obtained using the NASA-TLX, it was found a high mental workload of the rectory of workers from UNIOESTE – Cascavel. And, a directly proportional relationship between the mental workload with the age, gender and time of service.